Sensiblement dansé vertigo « Variations sur le sensible » chorégraphiées par Marjana Krajač (Itinera, 2017)
Marjana Krajač is currently one of the most remarkable Croatian choreographers; she explores in her work Variations on Sensitive (Varijacije o osjetnom, 2014) the meanings of sensible by activating a shared sensibility equally among the five dancers: by touching, watching, moving, and by their long performing exposability (lasting almost three hours) in front of the audience. Through the movement that is both powerful and fragile, insisting to go to the core of the dancing gesture, Marjana Krajač weaves complex networks of questions on the incursion of sensitive matter in the choreographic tissue as well as on the act of the dance performance itself. This essay on Variations on Sensitive choreographed by Marjana Krajač propose that the recent works of this artist could be called “posthybrid dance”. This is to highlight the choreographer’s decision to build this performance with dance itself, at the same time evidently aware of the historical and present-day dance creators who directly or indirectly interweave her artistic thought.